Differential effects of 7 and 16 groups of muscle relaxation training following repeated submaximal intensity exercise in young football players - Sharifah Maimunah, S. M. P.; Hashim, H. A. (Perceptual and Motor Skills, 2016)
This study compares two versions of progressive muscle relaxation (PMR) training (7 and 16 muscle groups) on oxygen consumption (VO2), heart rates, rating of perceived exertion and choice reaction time. Football (soccer) players (N = 26; M age=13.4yr., SD = 0.5) were randomly assigned to either 7 muscle groups PMR, 16 muscle groups PMR, or a control group. PMR training requires the participants to tense a muscle, hold the muscle contraction, and then relax it. Measurement was conducted prior to and after the completion of 12 sessions of PMR. The dependent variables were measured following four bouts of intermittent exercise consisting of 12 min. of running at 60% V02max for 10 min. followed by running at 90% V02max for 2 min. with a 3-min. rest for each bout. Lower VO2, heart rate, perceived exertion, and quicker reaction time were expected in both relaxation groups compared to the control group. The results revealed a significant reduction in heart rates and choice reaction time for both relaxation groups, but the longer version produced significantly quicker choice reaction time.